Labour market power and between-firm wage (in)equality - Matthias Mertens (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2021)
I study how labour market power affects firm wage differences using German manufacturing sector firm-level data (1995-2016). In past decades, labour market power increasingly moderated rising between-firm wage inequality. This is because high-paying firms possess high and increasing labour market power and pay wages below competitive levels, whereas low-wage firms pay competitive wages. Over time, large, high-wage, high-productivity firms generate increasingly large labour market rents while selling on competitive product markets. This provides novel insights on why such "superstar firms" are profitable and successful. Using micro-aggregated data covering most economic sectors, I validate my results for ten other European countries.
Keywords: J31; J42; L10; 330; inequality; labour market power; monopsony; rent-sharing; superstar firms